The mouth and the ego’s problem - Sánchez Mayor, Paula (Escritura e Imagen, 2019)
The proposal of this article is to go through the last pages of Ego sum, a boof by Jean-Luc Nancy published in 1979, locating there the problem of the union of the soul ante the body and keeping in mind the reading of Derrida in El tocar, Jean-Luc Nancy, mainly the criticism that makes Nancy in relation to the mouth as a place of intersection of the soul and the body. This course aims to outline the first steps that lead to the understanding os the subject in Nancy’s thought.